Myoepithelial Cell Contraction and Milk Ejection Are Impaired in Mammary Glands of Mice Lacking Smooth Muscle Alpha-Actin - Haaksma, Carol J. (Society for the Study of Reproduction, Inc., 2011)
Mammary myoepithelial cells are specialized smooth musclelike epithelial cells that express the smooth muscle actin isoform: smooth muscle alpha-actin (ACTA2). These cells contract in response to oxytocin to generate the contractile force required for milk ejection during lactation. It is believed that ACTA2 contributes to myoepithelial contractile force generation; however, this hypothesis has not been directly tested. To evaluate the contribution of ACTA2 to mammary myoepithelial cell contraction, Acta2 null mice were utilized and milk ejection and myoepithelial cell contractile force generation were evaluated. Pups suckling on Acta2 null dams had a significant reduction in weight gain starting immediately postbirth. Cross-fostering demonstrated the lactation defect is with the Acta2 null dams. Carmine alum whole mounts and conventional histology revealed no underlying structural defects in Acta2 null mammary glands that could account for the lactation defect. In addition, myoepithelial cell formation and organization appeared normal in Acta2 null lactating mammary glands as evaluated using an Acta2 promoter-GFP transgene or phalloidin staining to visualize myoepithelial cells. However, mammary myoepithelial cell contraction in response to oxytocin was significantly reduced in isolated Acta2 null lactating mammary glands and in in vivo studies using Acta2 null lactating dams. These results demonstrate that lack of ACTA2 expression impairs mammary myoepithelial cell contraction and milk ejection and suggests that ACTA2 expression in mammary myoepithelial cells has the functional consequence of enhancing contractile force generation required for milk ejection.